(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In recent years, the emphasis on the study and teaching of foreign languages ​​has increased significantly. This is done to make foreign language lessons, especially English, more interesting, that is, using a variety of innovative methods, techniques and interactive games that challenge a wide variety of students. Using these games throughout the lesson further enhances students’ interest in learning the subject. This article describes techniques for learning English and Russian through games.